A Quantitative Methodology to Enhance a Strategy Map - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L; Moraga-Correa, J (Elsevier B.V., 2020)
This paper presents a methodology to improve the identification of causal relationships of an existing strategy map of a company, using a multi-decision criteria method. A strategy map is one of the components of a balanced scorecard (BSC). It contains strategic objectives grouped into four perspectives and the cause-effect link between those objectives. There is no “standard” method for identifying those relationships. In many companies, they are identified conceptually, using the experience and knowledge of the company s managers. Even though, the literature presents a number of articles using multicriteria decision methods to model a balanced scorecard, only a few of them deal with the identification of the causal relationships. However, t is assumed (by the authors) that the strategy map obtained using their method is better than strategy map that would have been obtained using only the judgment of managers. This paper does not assume that and this is the reason why the existing strategy map (or a map obtained using a qualitative approach) is combined with a map obtained by using a quantitative method to arrive to a final strategy map. This is the contribution of the paper. The method uses the Decision-making Trial and Evaluation Laboratory (DEMATEL) method to identify the relationships of a strategy map. Then the resulting map is compared with the existing strategy map (or a map obtained using a qualitative approach). To identify the similarities and differences the K-means clustering method is used. From those similarities and differences found, it is decided which causal relationships will be included in the final strategy map. As an illustration, the application of the proposed methodology in a manufacturing company is shown. © 2019 Elsevier B.V.